2009
DOI: 10.1136/vr.165.11.319
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mycoplasma bovigenitalium and Mycoplasma canadense from outbreaks of granulopapular vulvovaginitis in dairy cattle in Israel

Abstract: A syndrome in which white foci and granulopustular lesions appeared on the vaginal mucous membranes of Holstein cows in several dairy herds in Israel is described. During clinical and diagnostic investigations, Mycoplasma bovigenitalium was isolated from 11 of 20 clinical cases. Vaginal swabs taken from the same cows yielded three isolates of Mycoplasma canadense, which were all associated with the M bovigenitalium infection. Two isolates of small, round, non-enveloped viral particles were approximately 25 nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 12 publications
0
9
0
4
Order By: Relevance
“…The lungs and internal organs from cows that died showing respiratory signs were tested for respiratory and systemic viral pathogens including parainfluenza virus type 3, bovine viral diarrhoea virus and bovine respiratory syncytial virus (Lynsyansky and others 2009, Friedgut and others 2011). The lungs were also tested for relevant bacterial pathogens such as Mycoplasma alkalescens , Mycoplasma bovis and Mannheimia haemolytica .…”
Section: Methodsmentioning
confidence: 99%
“…The lungs and internal organs from cows that died showing respiratory signs were tested for respiratory and systemic viral pathogens including parainfluenza virus type 3, bovine viral diarrhoea virus and bovine respiratory syncytial virus (Lynsyansky and others 2009, Friedgut and others 2011). The lungs were also tested for relevant bacterial pathogens such as Mycoplasma alkalescens , Mycoplasma bovis and Mannheimia haemolytica .…”
Section: Methodsmentioning
confidence: 99%
“…As its name suggests M. bovigenitalium has been described in cattle and it has been isolated from the reproductive tract, pneumonic, arthritic and mastitic cattle as well as aborted foetuses [9] . Lysnyansky et al [10] identified M. bovigenitalium and Mycoplasma canadense from outbreaks of granulopapular vulvovaginitis in dairy cattle in Israel and Catania et al [6] reported M. bovigenitalium from infertile cattle. There are also reports describing the isolation of M. bovigenitalium and M. arginini from the genital tract of goats [8] and semen of naturally infected asymptomatic rams [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the presence of Mycoplasma species in the genital tracts of diseased and healthy cows (26)(27)(28). Genital infections caused by mycoplasmas are generally asymptomatic but have been reported to be the most important cause of infertility (26,28).…”
Section: Discussionmentioning
confidence: 99%